Pengelolaan Administrasi Keuangan Daerah dan Implikasinya terhadap Kinerja Organisasi Publik: (Studi pada Dinas PUPR Aceh) - Depita Kardiati; Risna Dewi; Ferizaldi Ferizaldi (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2026)
Regional financial administration management is a strategic aspect in realizing good governance and supporting the improvement of public organizational performance. However, in practice, there remains a gap between administrative compliance and the effectiveness of financial management implementation. This study aims to analyze regional financial administration management and examine its implications for public organizational performance at the Department of Public Works and Spatial Planning (PUPR) of Aceh Province. This research employs a qualitative approach with a descriptive type. Data collection techniques include in-depth interviews, observation, and documentation studies. Data analysis consists of data reduction, data presentation, and conclusion drawing. The results indicate that, normatively, financial administration management has been implemented in accordance with regulations; however, substantively it is not yet fully optimal. This is reflected in fluctuations in budget absorption, particularly in direct expenditure, delays in reporting, and shifts in the implementation schedule of activities. The main factors influencing these conditions include limited human resources, weak time management, and suboptimal coordination among work units. The implications of these conditions are seen in the suboptimal effectiveness of programs, budget efficiency, and timeliness in achieving organizational targets. This study emphasizes that regional financial management should not only focus on administrative compliance but also be directed toward a performance-based approach to enhance public service quality and achieve organizational goals.